THE INFLUENCE OF SALES GROWTH, CAPITAL INTENSITY, AND CORPORATE SOCIAL RESPONSIBILITY TO TAX AGGRESSIVENESS CASE STUDIES OF MANUFACTURING COMPANIES REGISTERED ON THE IDX 2014-2018 - Ambarjati, Laurensia Hanny; Siswoadmojo, Sistomo; Regina, Desideria (Fundamental Management Journal, 2021)
The purpose of this research is to see whether there is an influence between sales growth, capital intensity, and corporate social responsibility on tax aggressiveness in manufacturing companies listed on the IDX in 2014-2018. This study uses a quantitative approach, and usesmultiple regression analysis to test sales growth, capital intensity, and corporate social responsibility towards tax aggressiveness. From the results of statistical tests, it is found that sales growth and capital intensity have no partial or significant effect on tax aggressiveness, while corporate social responsibility has a partial and significant effect on tax aggressiveness.Keywords: Sales Growth, Capital Intensity, tax aggressiveness